The icepick surgeon : murder, fraud, sabotage, piracy, and other dastardly deeds perpetrated in the name of science - Kean, Sam (Little, Brown and Company, 2021)
"Science is a force for good in the world--at least usually. But sometimes, when obsession gets the better of scientists, they twist a noble pursuit into something sinister. Under this spell, knowledge isn't everything, it's the only thing--no matter the cost. Bestselling author Sam Kean tells the true story of what happens when unfettered ambition pushes otherwise rational men and women to cross the line in the name of science, trampling ethical boundaries and often committing crimes in the process"--